Private Health Insurance Status and Utilisation of Dental Services in Australia - Hopkins, Sandra; Kidd, M.; Ulker, A. (Wiley-Blackwell Publishing Asia, 2013)
This article focuses on the relationship between private insurance status and dental service utilisation in Australia using data between 1995 and 2001. This article employs joint maximum likelihood to estimate models of time since last dental visit treating private ancillary health insurance (PAHI) as endogenous. The sensitivity of results to the choice between two different but related types of instrumental variables is examined. We find robust evidence in both 1995 and 2001 that individuals with a PAHI policy make significantly more frequent dental consultations relative to those without such coverage. A comparison of the 1995 and 2001 results, however, suggests that there has been an increasing role of PAHI in terms of the frequency of dental consultations over time. This seems intuitive given the trends in the price of unsubsidised private dental consultations. In terms of policy, our results suggest that while government measures to increase private health insurance coverage in Australia have been successful to a significant degree, that success may have come at some cost in terms of socio-economic inequality as the privately insured are provided much better access to care and financial protection.